Studi Analisis dan Perancangan Sistem E-Innovation dengan Menggunakan Voting dan Analytical Hierarchy Process untuk Menampung Ide Inovasi di Dinas Perdagangan dan Perindustrian Kota Surabaya - Adhika Dwi Pramudita; Rinabi Tanamal (Jurnal Manajemen dan Bisnis Indonesia, 2016)
The problem is how to design and make E-Innovation technology prototype using Analytical Hierarchy Process. The purpose of this project is designing and making the E-Innovation prototype which gives solution to increase quantity and quality of Innovation ideas at Dinas Perdagangan dan Perindustrian Kota Surabaya. The Methods used to design and making the E-Innovation prototype are interview, observation, and experiment. The goal is to increase quantity and quality of Innovation ideas at Dinas Perdagangan dan Perindustrian Kota Surabaya. Keywords: Dinas Perdagangan dan Perindustrian Kota Surabaya, Innovation, E-Innovation, Analytical Hierarchy Process.